KEMAMPUAN GURU DALAM MENYAMPAIKAN MATERI SURAH AL-KAFIRUN PADA MATA PELAJARAN AL-QUR’AN HADITS KELAS VI MI MAMBAUL ULUM PUNGGUR KECIL - IMAM SANUSI (Fakultas Agama Islam Universitas Billfath, 2020)
The author is interested in researching this in order to find out: 1) the ability of teachers to deliver learning materials that are facts, 2) conceptual, 3) principles, 4) and procedural in the subject of Al-Qur'an Hadith Class VI at MI Mambaul Ulum Punggur Kecil Academic Year 2019/2020 with the subject matter